A case study of the use of GPR for rehabilitation of a classified Art Deco building: The InovaDomus house - Nuno Barraca (2016)
Ancient buildings in historical town centers can be protected by Cultural Heritage legislation, thus implying that any rehabilitation must respect their main architectural features. These concerns also apply to Modern and Contemporary buildings, in particular if they are important examples of architectural styles from those periods. These extra problems, or motivations, add to the inherent structural delicacy of ancient building restoration that requires detailed knowledge of the building foundations, characteristics and materials, modification history, infrastructure mapping, current pathologies, etc., all relevant information for an informed rehabilitation project. Such knowledge is seldom available before the actual rehabilitation works begin, and the usual invasive preliminary surveys are frequently expensive, time-consuming and likely significantly alter/damage the building's main features or structural integrity. Hence, the current demand for indirect, non-invasive, reliable and high resolution imagery techniques able to produce relevant information at the early stages of a rehabilitation project. The present work demonstrates that Ground Penetrating Radar (GPR or Georadar) surveys can provide a priori knowledge on the structure, construction techniques, materials, history and pathologies in a classified Modern Age building. It is also shown that the use of GPR on these projects requires carefully designed surveys, taking into account the known information, spatial constraints, environmental noise, nature and dimensions of the expected targets and suitable data processing sequences. Thus, if properly applied, GPR produces high-resolution results crucial for sound engineering/architectural interventions aiming to restore and renovate Modern and Contemporary buildings, with (1) focus on the overall quality of the end-result, (2) no damage inflicted to the existing structure, (3) respect of the building's historical coherence and architectural elements and characteristics, that is, its Cultural Heritage value. Most of the findings and applications discussed in this work can be seen as an approximation to model studies, so that, relevant information can be drawn from the different investigated situations. Therefore, owing to the nature and the range of the problems encountered in this case study, it is also expected that the presented GPR data and interpretation will provide important clues and guidance in the planning and investigation of similar projects and problems.